Traces of Pre-Islamic Syncretism in Local Culture: Reconstruction of The Religious Identity of The Indonesian Archipelago - Syafira Nur Alfionisa; Nindia Pitaloka; Naila Dhiya Ulhaq (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2025)
This study analyzes the dynamics of pre-Islamic syncretism in the Indonesian archipelago by examining the interaction and assimilation of animism and dynamism with Hinduism and Buddhism, as well as their manifestations in social and ritual life and their continuing cultural legacy. Using a descriptive qualitative approach, this research seeks to capture the complex and contextual patterns of syncretism that shaped early Indonesian society. The study is based on secondary data drawn from scientific journals, academic articles, books, and other scholarly publications collected through library research. Data were analyzed using content analysis and thematic analysis, involving data reduction, interpretation, and categorization. The findings reveal that the interaction between animism, dynamism, and Hindu-Buddhist traditions formed a fundamental basis for early religious and cultural identity in Indonesia, resulting in a syncretic framework that structured social practices and belief systems. This framework later facilitated the integration of Islam in an accommodative and peaceful manner with local traditions. The legacy of pre-Islamic syncretism remains evident in contemporary practices such as grave pilgrimages, selametan rituals, and Islamic architectural forms, which continue to function as socio-cultural foundations supporting religious tolerance and moderation in modern Indonesian society.